Experimental Studies on the Influence of Plasma Treatment of Polyethylene in Carbon Fiber Composites: Mechanical and Morphological Studies - K R, Sumesh; Anton, Jakub; Spatenka, Petr; Sourkova, Hana Jelinek (Polymers, 2022)
This research focused on enhancement of mechanical properties in carbon fiber (CF)-filler-reinforced linear low-density polyethylene (PE) matrix composites. A hand layup method using an oven was used as the fabrication method. Improvement in adhesion was achieved by oxygen plasma treatment to the PE matrix. CF and PE were initially mixed by normal stirring, ultrasonication and mechanical stirring before being filtered and dried for fabrication. Better tensile results were observed with a plasma-treated polyethylene (PEP)/10 wt.% CF combination, with a maximum tensile strength of 21.5 MPa and improvement in the properties of up to 12.57% compared to non-plasma PE with the same CF addition. The addition of carbon fibers at 13 and 15 wt.% resulted in a reduction in the tensile strength properties to 18.2 MPa and 17.7 MPa, respectively. This reduction in tensile strength was due to agglomeration of CF with plasma- and non-plasma-treated PE. The fabrication condition of 180 °C temperature for 20 min showed better tensile properties than other conditions. The SEM results following tensile testing revealed enhanced CF filler adherence with plasma PE results, as well as fewer surface deformations. A higher flexural strength of 25.87 MPa was observed for the plasma treated PE/7 wt.% CF combination.
Keywords: mechanical properties; polyethylene; carbon fiber; plasma treatment